IMPROVING ENGLISH SPEAKING SKILLS THROUGH THE DEBATE METHOD FOR GRADE XI STUDENTS - Peni Astuti; Ina Anifatul Mustainah; Alindia Firda; Amir Hamzah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
Abstract This classroom action research aimed to improve the English speaking skills of eleventh-grade students through the implementation of the debate method. The study was conducted at SMAN 1 Waringinkurung during the first semester of the 2025/2026 academic year and involved 40 students as research participants. The research was motivated by students’ low speaking performance, limited confidence, and minimal opportunities to actively participate in oral communication during English lessons. The study was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through speaking tests, observation sheets, and documentation. The findings revealed a significant improvement in both students’ speaking skills and classroom participation. Students’ activeness increased from 60% in Cycle I to 85% in Cycle II, while the percentage of students achieving the Minimum Mastery Criterion improved from 57.5% to 82.5%. The results indicate that the debate method effectively enhances students’ confidence, fluency, and ability to express ideas orally. Therefore, the debate method can be considered an effective and communicative instructional strategy for improving English speaking skills at the senior high school level. Keywords: speaking skills, debate method, classroom action research, EFL students AbstrakPenelitian tindakan kelas ini bertujuan untuk meningkatkan keterampilan berbicara dalam bahasa Inggris melalui penerapan metode debat pada siswa kelas XI SMAN 1 Waringinkurung. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan berbicara siswa yang disebabkan oleh kurangnya kepercayaan diri, keterbatasan kesempatan berbicara, serta pembelajaran yang masih berpusat pada guru. Penelitian dilaksanakan pada semester ganjil tahun ajaran 2025/2026 dengan melibatkan 40 siswa sebagai subjek penelitian. Penelitian dilakukan dalam dua siklus yang masing-masing meliputi tahap perencanaan, tindakan, observasi, dan refleksi. Data penelitian dikumpulkan melalui tes keterampilan berbicara, lembar observasi keaktifan siswa, dan dokumentasi. Hasil penelitian menunjukkan adanya peningkatan yang signifikan pada keterampilan berbicara dan keaktifan siswa. Persentase keaktifan siswa meningkat dari 60% pada siklus I menjadi 85% pada siklus II, sedangkan ketuntasan keterampilan berbicara meningkat dari 57,5% menjadi 82,5%. Temuan ini menunjukkan bahwa metode debat efektif dalam meningkatkan kepercayaan diri, kefasihan, dan kemampuan siswa dalam menyampaikan pendapat secara lisan. Dengan demikian, metode debat dapat dijadikan sebagai alternatif strategi pembelajaran yang komunikatif untuk meningkatkan keterampilan berbicara bahasa Inggris di tingkat SMA. Kata kunci: keterampilan berbicara, metode debat, penelitian tindakan kelas, siswa SMA